Aortopexy for the treatment of tracheomalacia in children: review of the literature - Torre Michele; Carlucci Marcello; Speggiorin Simone; Elliott Martin J (BMC, 2012)
Abstract Severe tracheomalacia presents a significant challenge for Paediatricians, Intensivists, Respiratory Physicians, Otolaryngologists and Paediatric Surgeons. The treatment of tracheomacia remains controversial, but aortopexy is considered by most to be one of the best options. We conducted a review of the English literature relating to aortopexy. Among 125 papers, 40 have been included in this review. Among 758 patients (62% males) affected with tracheomalacia, 581 underwent aortopexy. Associated co-morbidities were reported in 659 patients. The most frequent association was with oesophageal atresia (44%), vascular ring or large vessel anomalies (18%) and innominate artery compression (16%); in 9% tracheomalacia was idiopathic. The symptoms reported were various, but the most important indication for aortopexy was an acute life-threatening event (ALTE), observed in 43% of patients. The main preoperative investigation was bronchoscopy. Surgical approach was through a left anterior thoracotomy in 72% of patients, while median approach was chosen in 14% and in 1.3% a thoracoscopic aortopexy was performed. At follow-up (median 47 months) more than 80% of the patients improved significantly, but 8% showed no improvement, 4% had a worsening of their symptoms and 6% died. Complications were observed in 15% of patients, in 1% a redo aortopexy was deemed necessary. In our review, we found a lack of general consensus about symptom description and evaluation, indications for surgery, though ALTE and bronchoscopy were considered by all an absolute indication to aortopexy and the gold standard for the diagnosis of tracheomalacia, respectively. Differences were reported also in surgical approaches and technical details, so that the same term "aortopexy" was used to describe different types of procedures. Whatever approach or technique was used, the efficacy of aortopexy was reported as high in the majority of cases (more than 80%). A subgroup of patients particularly delicate is represented by those with associated gastro-esophageal reflux, in whom a fundoplication should be performed. Other treatments of tracheomalacia, particularly tracheal stenting, were associated with a higher rate of failure, severe morbidity and mortality. Non english abstract La tracheomalacia severa rappresenta una sfida per Pediatri, Intensivisti, Pneumologi, Otorinolaringoiatri, Chirurghi Pediatri. Il trattamento della tracheomalacia è tuttora controverso. L'aortopessi è considerata da molti la migliore opzione terapeutica. Abbiamo condotto una revisione della letteratura di lingua inglese su tale argomento. Di 125 lavori, 40 sono stati inclusi nella revisione. Tra 758 pazienti (62% maschi) affetti da tracheomalacia, 581 sono stati sottoposti ad aortopessi tra il 1968 e il 2008. In 659 pazienti alcune comorbidità erano presenti. L'associazione più frequente era con l'atresia esofagea (44%), l'anello vascolare o un'anomalia dei grossi vasi (18%), la compressione da parte dell'arteria innominata (16%); nel 9% la tracheomalacia era idiopatica. I sintomi riportati sono stati variabili, ma l'indicazione più importante all'aortopessi sono stati eventi di ALTE, osservati nel 43% dei pazienti. Lo studio diagnostico preoperatorio principale è stato la broncoscopia. L'approccio chirurgico è avvenuto attraverso una toracotomia anteriore sinistra nel 72% dei pazienti, mentre un approccio mediano è stato scelto nel 14% e nell'1.3% dei casi è stato eseguito un approccio toracoscopico. Al follow-up (mediana di 47 mesi) la maggioranza dei pazienti sono migliorati significativamente, ma l'8% di essi non è migliorato, il 4% è peggiorato e il 6% è morto. Complicazioni sono state riportate nel 15% dei pazienti, nell'1% un nuovo intervento di aortopessi è stato necessario. In questa revisione abbiamo trovato che non c'è un consenso generale sulla valutazione e sulla descrizione dei sintomi, sulle indicazioni chirurgiche ed esami preoperatori, anche se le ALTE e la broncoscopia venivano considerate rispettivamente un'indicazione assoluta all'aortopessi e il "gold standard" diagnostico per la tracheomalacia. Venivano riportate differenze negli approcci chirurgici e nei dettagli tecnici, e lo stesso termine di aortopessi veniva usato per indicare diverse procedure chirurgiche. In ogni caso, indipendentemente dall'approccio o tecnica utilizzati, l'efficacia dell'aortopessi veniva riportata come elevata nella maggioranza dei casi (più dell'80%). Un sottogruppo di pazienti particolarmente delicato è rappresentato da quelli con reflusso gastroesofageo associato, nei quali sarebbe indicata una fundoplicatio. Altri trattamenti della tracheomalacia, quali stent tracheale, sembrano gravati da una maggiore percentuale di insuccessi, morbidità severa e mortalità.